Cecal Volvulus - Hasbahceci, Mustafa (Springer-Verlag, 2012)
A twisted loop of the bowel and its mesentery on a fixed point is known as volvulus and it may arise more frequently in the sigmoid colon and cecum. Cecal volvulus as an uncommon cause of acute intestinal obstruction is axial twist of the cecum, ascending colon and terminal ileum around their mesenteric pedicles. Although there are many different etiologic and predisposing factors for cecal volvulus, exact etiology is most likely multifactorial in presence of mobile cecum. Its clinical presentation is highly variable, ranging from intermittent episodes of abdominal pain to abdominal catastrophe depending on pattern, severity and duration of cecal volvulus causing intestinal obstruction. Due to its rarity and nonspecific presentation, preoperative diagnosis is rarely achieved in most cases. Abdominal radiographs as an initial diagnostic test are usually abnormal and can detect cecal volvulus in half of cases. Nowadays, computerized tomography is used for more accurate diagnosis and differentiation from other acute emergent conditions. Resection with right hemicolectomy and primary ileocolic anastomosis has been recommended for surgical treatment of cecal volvulus.